(untitled) (Muitas Vozes, 2022)
Nineteenth-century England presents itself as the social context for the beginning of the industrial revolution, which promotes technological, material and production means development. Consequently, this same prosperity model drives the emerging capitalism of the time, increasing the difference between classes, where highly patriarchal and exclusionary values prevail. In such historical clipping, Oscar Wilde appears: dandy, flaneur, who breaks with the aristocratic conformism to which he could have safely accommodated himself, preferring to use wit and talent to express a worldview that values beauty and satirizes the status quo of his time. The general theme of this article encompasses several aspects of moral nature defined in Oscar Wilde’s comedies of society. Such aspects deal with social criticism in texts that question the aristocratic system prevailing in Victorian England. It is explored, therefore, about the false morality satirized by Wilde, approaching the Victorian institutions that corroborated and fortified the questionable morals and the patriarchal system of the time, exposing the fragility of its said virtues.